Globalisation as a 'good times' phenomenon: a search-based explanation - T. Huw Edwards (Kiel Institute for the World Economy (IfW), 2009)
Globalisation is associated with long periods of sustained economic growth and credit expansion, whereas major recessions tend to lead to falling trade and protectionism. The sensitivity of trade to global economic conditions is not simply driven by policy: rather, in a model of costly search, firms who are engaged in a searching process are very sensitive to changing economic circumstances. In turn, this causes protectionism to be partly endogenous, since optimal noncooperative tariffs can be high during periods when the sensitive, searching firms have exited the market.
Keywords: F15; F43; 330; Globalisation; trade; search; Globalisierung; Wirtschaftswachstum; Internationale Handelspolitik; Informationskosten; Theorie